ANALISIS PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DALAM MENCEGAH FRAUD (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The cause of this study is to examine and take a look at the effect of public sector accounting at the accountability of public authorities inside the location of fraud prevention. This take a look at makes use of a quantitative approach. The website of this look at became conducted in authorities places of work within the city of Malang. This have a look at might be performed in October 2021 until it's miles completed. The populace on this take a look at consists of authorities agencies located in the metropolis of Malang. Sampling became done using a focused sampling method with predetermined criteria to achieve 57 samples. The effects of the study kingdom that public region accounting has a substantial effect at the responsibility of public establishments, the responsibility of presidency agencies has a considerable impact on fraud prevention, public region accounting has a enormous effect on fraud prevention, and public region accounting has a sizable impact on fraud prevention through accountability of public establishments for overall performance.Keywords: public area accounting, duty and fraud inside the performance of public establishments